The Role of Character Education in Overcoming Juvenile Delinquency in Motorcycle Gangs in Hamlet XII, Muliorejo Village, Sunggal District, Deli Serdang Regency - Ramadhan, Aldimas; Hemawati, Hemawati; Pasaribu, Syahrin (Lembaga Riset Mutiara Akbar, 2024)
Talking about teenagers is very interesting because teenagers are the next generation of religion and nation, so the safety of the nation lies in the hands of today's teenagers. Based on research that I observed, from January 2024 to April 2024, especially in Hamlet This makes society uneasy, namely it can be called a motorbike gang association. This will have a negative impact on the current generation of teenagers, where teenagers should be able to join more useful associations, so that they don't end up joining the wrong associations. Therefore, this article will dissect what educators and parents can do to shape the character education of teenagers and how to deal with teenagers today.